SPECIAL ISSUE : "Integrative medicine in oncology: another step forward" - NUTRITIONAL ONCOLOGY TEAM EMPOWERMENT (NOTE): A BOWEN FRAMEWORK-BASED PROJECT IN GASTROINTESTINAL CANCERS - Roberto Bordonaro; Rosella Guggino; Dario Piazza; Alessio Filippone; Maria Maddalena Rossi; Vittorio Gebbia (Journal of Cancer Rehabilitation, 2021)
Background Most oncology units underestimate the prevalence of cancer-related malnutrition (CRM) and its negative consequences even in western countries. Various studies have reported a prevalence of CRM ranging from 25% to over 70% based on nutritional assessments. This paper describes the feasibility of implementing an innovative, multi- disciplinary, multi-site nutrition-based oncology program among oncological centers in Sicily. Methods This project is a pre-post feasibility observation analysis to assess an oncology rehabilitation program’s viability based on Bowen’s Framework according to the Template for Intervention Description and Replication checklist. These feasibility guidelines describe eight domains to be addressed: acceptability, demand, implementation, practicality, adaptation, integration, expansion, and limited-ef cacy testing. Results Eighteen medical oncologists from twelve medical oncology units actively participated in the educational sessions. Other participants included eight radiation oncologists from seven radiotherapy units, eight surgeons, including one head/neck specialist, and six internal medicine/nutritionists for a total of thirty-nine health-professionals. Acceptability was high since the participation rate was 88%. During the two months interval between the web-based implementation events, there was a ten-fold increase in the number of oncology centers that started a nutritional screening program and the number of patients referred to a nutritionist. This increase showed a statistical signi cance (Fisher exact p< 0.00001). Patients’ satisfaction, evaluated with a simple 5-point Likert scale, was > 4 in 84% of interviewed patients. Conclusion This implementation program showed high acceptability among oncologists and a high degree of patients satisfaction. A further step is to implement this high-quality process in the large volume cancer centers and create an ef cient network with smaller institutions according to a cooperative hub and spoke model. This program also includes elaborating a multi-institutional, multidisciplinary tumor board to coordinate treatment decisions in the network.